Relationship of metabolic syndrome defined by IDF or revised NCEP ATP III with glycemic control among Malaysians with Type 2 Diabetes - Riyadh Saif-Ali (Diabetology & Metabolic Syndrome, 2020)
Abstract Background The chronic complications of Type 2 Diabetes (T2D) such as macrovascular disease is amplified with the increase in the number of metabolic syndrome (MetS) risk factors. This research aims to study the relationship of MetS, diagnosed by the International Diabetes Federation (IDF) or revised National Cholesterol Education Programs Adult Treatment Panel III (NCEP ATP III) criteria, with glycemic control, fasting blood glucose (FBG), glycated hemoglobin (HbA1c), C-peptide, and insulin resistance in T2D patients. Methods The study is a cross-sectional observational study which, involved 485 T2D patients who are receiving treatment at the University Kebangsaan Malaysia Medical Center (UKMMC), Kuala Lumpur, Malaysia. The MetS among the T2D patients was diagnosed based on IDF and revised NCEP ATP III criteria. C-peptide and HbA1c levels were determined by an automated quantitative immunoassay analyzer and high-performance liquid chromatography, respectively. The MetS factors; FBG, triglyceride, and high-density lipoprotein cholesterol were measured by spectrophotometer. Results Application of the IDF and revised NCEP ATP III criteria respectively resulted in 73% and 85% of the T2D subjects being diagnosed with MetS. The concordance of these criteria in diagnosing MetS among T2D patients was low (κ = 0.33, P < 0.001). Both IDF and revised NCEP ATP III criteria indicated that T2D patients with 5 MetS factors had higher insulin resistance (P = 2.1 × 10−13; 1.4 × 10−11), C-peptide (P = 1.21 × 10−13; 4.1 × 10−11), FBG (P = 0.01; 0.021), and HbA1c (P = 0.039; 0.018) than those T2D patients without MetS, respectively. Conclusion Although there is a low concordance between IDF and revised NCEP ATP III criteria in the diagnosis of MetS among T2D patients, both criteria showed that T2D patients with 5 MetS factors had higher insulin resistance, C-peptide, FBG, and HbA1c.